51 Coronary sinus as predictor of atrial flutter in patients with narrow complex tachycardia. (28th September 2016) - Alkhalil, M; Kearney, A; Gregory, R; Cromie, N
Abstract : Introduction: Manoeuvres such as Valsalva or adenosine injection are routinely applied in patients presenting with narrow complex tachycardia (NCT). However, such manoeuvres could not be applied in short burst of NCT on telemetry or holter monitoring. Thereby, precise diagnosis of the underlying rhythm may not be identified until invasive electro physiology study is performed. Such delays, potentially for few weeks, may put patients with undiagnosed atrial flutter at significant risk of developing thromboembolism. Therefore, other tools are needed to aid diagnosis and potentially management of NCT. We sought to establish whether coronary sinus measurement (diameter) would prove to be a useful predictor for the diagnosis of atrial flutter for patients with NCT. Methods: A retrospective analysis of all consecutive patients who were referred to invasive electro physiology study following an episode of NCT between April 2013 and March 2014. CS size was measured blindly from EPs results and was recorded in end diastole using transthoracic echocardiography. Patients were divided into two groups: atrial flutter and non-flutter group. Statistical analysis was performed using SPSS 22.0. Results: Total of 90 patients were identified and coronary sinus was identified in 80% of patients. Pulmonary vein isolation cases were excluded from the analysis. Patients who have potential risk of developing thromboembolism i.e., CHA2 DS2 -VASc 1) were only included in this analysis. Mean age was 55 ± 21, 40.4% males with mean CS of 7.4 mm. There was no significant difference between the flutter and non-flutter groups in terms of right ventricle size and function, left ventricle ejection fraction, left ventricle end diastolic diameter, symptoms duration or CHA2 DS2 -VASc score. Atrial flutter group were are older and less likely to be females. They also have statistically significant larger coronary sinus (8.3 versus 6.7 mm, p = 0.007, Figure 1 ). On univariable logistic regression analysis age, female gender, coronary sinus diameter and right atrial size were all predictors of atrial flutter (see Table ). However, coronary sinus was the only independent predictor of atrial flutter diagnosis (OR 1.58, CI: 1.01–2.48, p = 0.046) using multivariable logistic regression analysis. Receiver Operating Characteristic area under the curve was 0.74 (p = 0.006) for the mean coronary size diameter of 7.4 mm to identify the flutter group (see Figure 2 ). Conclusion: Coronary sinus might be a useful tool to predict atrial flutter in patients with NCT who are at risk of developing thromboembolism. It is a non-invasive simple marker which could be measure using echocardiogram.